Long-term outcomes of drug-coated balloons in patients with diffuse coronary lesions - Yang, Xinyue; Lu, Wenjie; Pan, Liang; Han, Zhanying; Pan, Sancong; Wang, Xi; Zhu, Yongjian; Shan, Yingguang; Peng, Meng; Qin, Peng; Zhang, Peisheng; Qin, Xiaofei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Drug-coated balloons (DCB), alone or in combination with drug-eluting stents (DES), may be used to treat diffuse coronary lesions. We aimed to explore the efficacy and safety of DCB in patients with coronary disease and diffuse lesions. Methods: Consecutive patients with diffuse coronary lesions (lesion length > 25 mm) who underwent DCB and/or DES between January 2015 and December 2019 were included in this prospective, observational, multicenter study. The DCB group (n=355) included patients (143 lesions, 39.7%) treated with the DCB-only strategy and those (217 lesions, 60.3%) treated with the hybrid strategy (DCB combined with DES). The DES group included 672 patients (831 lesions) treated with DES alone. Target lesion revascularization (TLR) was the primary outcome of interest. The secondary outcome was major adverse cardiac events (MACE), defined as a composite of all-cause death, non-fatal myocardial infarction, and target vessel revascularization. Results: The two groups had comparable baseline clinical and lesion characteristics. Lesion length was similar (43.52 ± 16.46 mm vs. 44.87 ± 15.80 mm, P = 0.181) but the stent length in the DCB group was significantly shorter (24.02 ± 23.62 mm vs. 51.89 ± 15.81 mm, P < 0.001). Ten lesions (2.8%) in the DCB group received bailout stents. Over 3 years of follow-up, no significant difference in TLR incidence between the groups (7.3% vs. 8.3%, log-rank P = 0.636) were observed. Incidence of MACE also did not differ significantly (11.3% vs. 13.7%, log-rank P = 0.324). No thrombosis events occurred in the DCB group, while four patients (0.6%) in the DES group experienced stent thrombosis (log-rank P = 0.193). Moreover, similar TLR and MACE rates were observed between DCB-only and hybrid strategies (TLR: 6.4% vs. 8.0%, log-rank P = 0.651; MACE: 11.4% vs. 11.2%, log-rank P = 0.884). Conclusions: Long-term outcomes showed that the efficacy and safety of the DCB strategy (DCB alone or combined with DES) are similar to those of DES alone in diffuse coronary lesions. These findings suggest that this strategy is a promising alternative for select patients with diffuse coronary lesions.